10 Jahre SCiRN - Ein Netzwerk zur weltweiten Erforschung schrumpfender Städte. - Wiechmann, Thorsten (Routledge, 2015)
At the beginning of the 21st century, the shrinking cities phenomenon is widespread all over the industrialized world, in particular in Europe, North America, and East Asia. To deal with the results of demographic, economic and physical contraction processes and to plan for the future of considerably smaller but nevertheless livable cities is one of the most challenging tasks for urban planners in the near future. The Shrinking Cities International Research Network, SCiRN founded 2004 under the aegis of the Institute of Urban and Regional Development at the University of California, Berkeley, is a worldwide research consortium of scholars and experts from various institutions pursuing research on shrinking cities in a global context. The founding of the network was in response to the observation that although the decline of cities and urban regions was a common issue for urban planners in different local contexts, there was little comparative research on this topic. Therefore, SCiRN's mission is to advance international understanding and promote scholarship about Population decrease in urban regions and urban decline, causes, manifestations, spatial variations, and effectiveness of policies and planning interventions to stave off decline. Today, the network comprises 30 members from 4 countries and a PhD Academy for early stage researchers. The work being developed by the network includes case studies of suburbs, cities, towns, and regions that are investigated through a common comparative framework.
10 Years SCiRN - 24 Network for the global research on Shrinking Cities.
Keywords: Stadtplanung; Stadtentwicklung; Schrumpfung; Stadtforschung; Planungswissenschaft; Wissenschaftler; Netzwerk